The Power of Genes: A Case of Unusually Severe Systemic Toxicity After Localized Hepatic Chemoembolization With Irinotecan-Eluted Microspheres for Metastatic Colon Cancer. (December 2014) - Cruz, Joseph E.; Saksena, Rujuta; Jabbour, Salma K.; Nosher, John L.; Hermes-DeSantis, Evelyn; Moss, Rebecca A.
Objective: To report a case of systemic irinotecan toxicity following regional transarterial chemoembolization with drug-eluting beads loaded with irinotecan (DEBIRI-TACE) in a patient later found to have a homozygous mutation for UGT1A1*28.Case Summary: An 80-year-old woman presented with a cecal colon cancer with synchronous metastases to the liver. After resection of the primary tumor, the patient underwent DEBIRI-TACE with 100 mg of irinotecan to treat the residual disease in the liver. A week after this procedure, the patient developed grade 4 neutropenia, and later, alopecia. Eventually, it was found that the patient had a mutation of UDP glucuronosyltransferase 1 family polypeptide A1 (UGT1A1), which provided a reasonable explanation for the observed reaction.Discussion: The toxic effects of irinotecan are well understood. Patients with genetic polymorphisms of the genes encoding for the enzyme UGT1A1 may have increased incidence of irinotecan-associated toxicities because of decreased clearance of the active metabolite SN38 via the glucuronidation pathway. To date, there have been limited publications describing systemic adverse events following TACE or DEBIRI-TACE and, based on a thorough literature search, none following these procedures in patients with UGT1A1 polymorphisms. Based on the scoring results of the Naranjo algorithm (7), we are confident in attributing the observed reaction to the patient's genetic polymorphism.Conclusion: Although genetic testing prior to the initiation of irinotecan therapy is not currently recommended, assessment of UGT1A1 polymorphism is warranted when severe adverse events typical of systemic therapy manifest following DEBIRI-TACE.